2020
DOI: 10.1002/jmv.25984
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in the development of hepatocellular carcinoma after direct‐acting antiviral therapy in patients with HCV infection

Abstract: Sex differences in the predictors for hepatocellular carcinoma (HCC) development after direct‐acting antiviral (DAA) therapy was investigated. DAA therapy was given to 1438 (663 male, 775 female) patients. Sex differences in the HCC development rate and the factors contributing to HCC development after DAA therapy were investigated. Male patients had a significantly higher cumulative HCC incidence (log‐rank test, P =  .007). On multivariate analysis, the fibrosis‐4 index (HR = 1.11; 95%CI, 1.042‐1.202, P =  .0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…Several studies have reported that males are at high risk of developing HCC after IFN-based therapy [ 23 , 24 ]. In the present results, sex difference also affected HCC recurrence after IFN-free DAA regimens [ 25 ]. As in some previous reports, in the present study, absence of SVR was strongly associated with recurrence after DAA therapy.…”
Section: Discussionmentioning
confidence: 69%
“…Several studies have reported that males are at high risk of developing HCC after IFN-based therapy [ 23 , 24 ]. In the present results, sex difference also affected HCC recurrence after IFN-free DAA regimens [ 25 ]. As in some previous reports, in the present study, absence of SVR was strongly associated with recurrence after DAA therapy.…”
Section: Discussionmentioning
confidence: 69%
“…Results from another two recently published studies are consistent with those reported by this second study by Kanwal et al [ 39 ] In a retrospective study, Tani et al [ 40 ] demonstrated that the 12- and 36-mo cumulative incidences of HCC were 1.88 and 6.00%, respectively. Similarly, Watanabe et al [ 41 ] reported 1- and 2-year cumulative incidences of HCC of 1.9 and 4.1%, respectively.…”
Section: Hcc Occurrence After Daa Therapymentioning
confidence: 80%
“…Despite using different inclusion criteria and study methods, these three cohort studies demonstrated that the presence of cirrhosis and the absence of SVR were the major risk factors of HCC occurrence in HCV patients[ 34 , 35 , 37 ]. A high FIB-4 index and posttreatment AFP were identified as independent factors that contributed to HCC occurrence in two recent studies[ 39 , 41 ].…”
Section: Risk Factors For De Novo and Recurrent Hcmentioning
confidence: 99%
“…In 5 studies, baseline FIB-4 was reported to be an independent risk factor for HCC occurrence. 34 , 40 , 47 , 50 , 59 Risk thresholds varied according to each study: Kanwal et al used the standard 3.25 cut-off, 34 whereas Iio et al used the 2.67 cut-off. 47 In the study by Watanabe et al, baseline FIB-4 predicted HCC in females, only.…”
Section: Predictors Of De-novo Hccmentioning
confidence: 99%
“… 47 In the study by Watanabe et al, baseline FIB-4 predicted HCC in females, only. 59 In addition, three Japanese studies reported that post-SVR FIB-4 (at EOT and at SVR12) and changes in FIB-4 independently predicted de-novo HCC. 50 , 55 , 60 Among investigated serological biomarkers of fibrosis was Wisteria floribunda agglutinin positive Mac-2 (WFA*M2BP), which was tested in the study by Nagata et al, reporting that WFA*M2BP assessed 24 weeks after EOT independently predicted de-novo HCC 55 ( Tables 5 and 6 ).…”
Section: Predictors Of De-novo Hccmentioning
confidence: 99%